The Synodality of the Ukrainian Greek Catholic Church After Vatican II: A Need of the Faithful and Challenge for the Roman Curia - Maria Ivaniv Lonchyna (Religions)
The Second Vatican Council and its Decree Orientalium Ecclesiarum played a significant role in the life of the Ukrainian Greek Catholic Church. Vatican II became a moment of unity as all the Ukrainian Greek Catholic bishops, including the newly released from exile Josyf Slipyj, gathered in Rome. The bishops had the unique opportunity to form a synod of bishops of the Ukrainian Greek Catholic Church. This synod would help to unite the UGCC faithful scattered around the world into one ecclesial structure and preserve their Eastern Catholic identity in the diaspora. The laity, theologians, and most bishops were in favor of convening the UGCC synod of bishops. However, many challenges arose after the council, as the Vatican Curia did not allow the Ukrainian bishops to form a synod. The decree Orientalium Ecclesiarum brought a new perspective to the understanding of the Eastern Catholic Churches and their ecclesiology. The decree was actively used in UGCC discussions to support the convocation of a UGCC synod. Unfortunately, the Vatican did not confirm the legal character of the document, and its canonical power with respect to the UGCC synod was questioned. This paper will analyze the discussions and argumentation of the Ukrainian patriarchal lay movement, theologian Victor Pospishil, bishops, the Roman Curia, and their role in the convocation of the UGCC synod in 1980.